Nomads and Pastoralism: Linkage with Biodiversity Conservation in Upper Mustang, Nepal - Pandey, M.R.; Chetri, M. (Our Nature, 2006)
In this paper we attempted to present a glimpse of linkage between the nomads living in the pasture of Upper Mustang and their role in biodiversity conservation. The nomadic rangeland in Upper Mustang region harbors endangered Trans-Himalayan species like snow leopard, lynx, brown bear, Tibetan wild ass, Tibetan argali etc. with a variety of birds. It also harbors various medicinal species endemic to the region. Nomads are completely dependent on the livestock for the sustenance of their livelihood. There are only nine nomads families residing in rangelands of Upper Mustang, among them three families are resided in Lo- Manthang Panga area whereas four families in Dhalung/Chhujung area and one each in Lauchhe/Dhaknak area and Ghami Lekh area. Seasonal grazing is a customary practice for all nomadic families. Interview with the nomads (N=9) reveals that the grass availability in the pastures is in decreasing trend. They reveal increase in the number of snow leopard and blue sheep whereas the population of Tibetan Gazelle is in decreasing trend. Rijiphuwa and Pika are the two sites in Dhalung/Chhujung area where snow leopard and grey wolf are the main problem creators. In Lauchhe area (summer pasture) and Dhaknak area (summer pasture), grey wolf and snow leopard are the main problem animals. In comparison to other pasture, the families of Dhalung/Chhujung area faces higher number of livestock losses. Nomads use their own traditional measures to protect their livestock against predators. Large flocks of goats/sheep often come from Tibet to Dhalung/Chhujung area which increases the pressure during the summer and is also the root cause for the deterioration of the pasture. The daily activities of Tibetan nomads have created disturbances resulting adverse impacts on the biodiversity. During summer, the habitat of Tibetan gazelle and Tibetan wild ass is badly affected. Key words: Biodiversity, conservation, nomad, pastoralism, Upper Mustang doi:10.3126/on.v3i1.333 Our Nature (2005) 3: 42-49